Herak Milošević – a cramer from Maleševac - Pekić, Radmilo B. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
In medieval time cramers represented one of the most important links in transport of goods and services.It is widely known that in Middle Ages goods were transported in caravans through land roads. Because of the transport medieval merchants made deals with organisers of caravans  called „cramers” or chiefs. The Cramers took responsibility to come at the specified time with a certain number of people and pack animals to load and transport the goods, sometimes passengers , to a specific destination.Organisors of caravans transport in medieval Dubrovnik most often were Vlachs—cattlemen, settled in nearby hinterland in the area of todays Herzegovina. Since their basic occupation was cattle breeding, they disposed with a large number of pack animals, necessary for transport. Numerous record of caravan trade and Vlachs cramers remained in the archives of Dubrovnik where, among others, the proud people of a mountain settlement Maleševac were distinguished.Based on published and unpublished material from the Dubrovnik’s archives and relevant literature, this work presents the caravan trade of a prominent cramer, Herak Milošević from Maleševac. Systemizing numerous data about the mentioned cramer, we endeavored to complement the current knowledge about caravan trade and Vlachs from Maleševac.